E-module Based on Blended Learning for Islamic Religious Education Learning - Sulaiman, Muhammad (Universitas Jambi, Indonesia, 2023)
Islamic religious education is teaching, guidance, and care for students, who are expected to understand, appreciate, and practice the teachings of Islam and make it a way of life for individuals and society. The Covid-19 pandemic changed the teaching patterns in class, giving birth to distance learning patterns facilitated by digital technology-based online learning media to deliver learning. One of the digital technology-based learning media that can make learning more meaningful is blended learning-based e-modules. This research aimed to develop e-modules based on blended learning that can be used in Islamic Religious Education learning and accessed through devices. The method used in this research was the research and development method with the ADDIE approach, which includes five stages, namely the needs analysis stage, the design stage, the development stage, the implementation stage and the evaluation stage. This e-module is written in a communicative language accompanied by pictures and videos. The e-module contains learning activities following the blended learning syntax. This research was to test the feasibility of the e-module. The validation test assessment was a Likert scale questionnaire with expert respondents (material and media) and trials with teacher and student respondents. The results of this research were blended learning-based e-modules, which were validated and tested. Based on the preliminary research results, the developed e-module was expected to be suitable as a meaningful learning medium for students.